Clinical utility of chromosomal microarray analysis and whole exome sequencing in foetuses with oligohydramnios - Shi, Xiaomei; Ding, Hongke; Li, Chen; Liu, Ling; Yu, LiHua; Zhu, Juan; Wu, Jing (Annals of medicine (Helsinki), 2023)
CMA has low diagnostic utility for oligohydramnios. WES offers obvious advantages for improving the detection over CMA, which improves pregnancy management, prenatal counselling and recurrence risk assessment for future pregnancies. To evaluate the clinical utility of chromosomal microarray analysis (CMA) and whole exome sequencing (WES) in foetuses with oligohydramnios. In this retrospective study, 126 fetuses with oligohydramnios at our centre from 2018 to 2021 were reviewed. The results of CMA and WES were analysed. One hundred and twenty-four cases underwent CMA and 32 cases underwent WES. The detection rate of pathogenic/likely pathogenic (P/LP) copy number variant (CNV) by CMA was 1.6% (2/124). WES revealed P/LP variants in 21.8% (7/32) of the foetuses. Six (85.7%, 6/7) foetuses showed an autosomal recessive inheritance pattern. Three (42.9%, 3/7) variants were involved in the renin-angiotensin-aldosterone system (RAAS), which are the known genetic causes of autosomal recessive renal tubular dysgenesis (ARRTD). CMA has low diagnostic utility for oligohydramnios, while WES offers obvious advantages in improving the detection rate. WES should be recommended for fetuses with oligohydramnios.